2011
DOI: 10.1089/fpd.2010.0622
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Chlorine Dioxide Gas onSalmonella entericaInoculated on Navel Orange Surfaces and Its Impact on the Quality Attributes of Treated Oranges

Abstract: Microorganisms, including pathogens of public health significance, have been shown to contaminate orange juice during the mechanical extraction of juice. The problem gets exacerbated when washed oranges have high initial microbial load, due to an insufficient postharvest treatment. The objective of this study was to investigate the reduction of Salmonella enterica on orange surfaces using ClO₂ gas treatments to achieve a 5 log reduction, consistent with the recommendations of the U.S. Department of Agriculture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 33 publications
2
12
0
Order By: Relevance
“…The result is in agreement with the study conducted by Bhagat et al . () on vapour‐phase decontamination (0.1–0.5 mg L −1 for 2–14 min) of S. enterica on navel orange surface, as well as with the study conducted by Trinetta et al . () on using high‐concentration‐short‐time ClO 2 gas treatment (2.0–10.0 mg L −1 for 10–180 s) to inactivate S. enterica spp.…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…The result is in agreement with the study conducted by Bhagat et al . () on vapour‐phase decontamination (0.1–0.5 mg L −1 for 2–14 min) of S. enterica on navel orange surface, as well as with the study conducted by Trinetta et al . () on using high‐concentration‐short‐time ClO 2 gas treatment (2.0–10.0 mg L −1 for 10–180 s) to inactivate S. enterica spp.…”
Section: Resultssupporting
confidence: 80%
“…The linear effects of both parameters, shown in Table 3 (for details of model fitting, see section Model fitting and validation), are positive, that is the population reduction increased as the ClO 2 gas level increased or treatment time lengthened. The result is in agreement with the study conducted by Bhagat et al (2011) on vapour-phase decontamination (0.1-0.5 mg L À1 for 2-14 min) of S. enterica on navel orange surface, as well as with the study conducted by Trinetta et al (2010) on using high-concentration-short-time ClO 2 gas treatment (2.0-10.0 mg L À1 for 10-180 s) to inactivate S. enterica spp. on Roma tomato surface, suggesting potential uses of gaseous ClO 2 for a commercial fumigation of some fruits and/or vegetables before packing.…”
Section: Effects Of Clo 2 Dosage and Treatment Timesupporting
confidence: 91%
“…Many studies have found GCD effective against food-borne pathogens such as Escherichia coli, Listeria monocytogenes, and Salmonella enterica in applications in the food-processing industry (Bhagat et al, 2011;Bhagat et al, 2010;Mahmoud et al, 2007;Mahmoud et al, 2008;Trinetta et al, 2010). GCD has also been proven effective against viruses even at relatively low concentrations with extended exposure times (Morino et al, 2009;Sanekata et al, 2010).…”
Section: Chlorine Dioxidementioning
confidence: 99%
“…The inclusion of a neutralizing step after contact with the antimicrobial, although previously recommended, is not a standard practice among researchers and varies among studies (4,10,11,15,19). Collins-Thompson and Jackson (8) recommended the use of ice-cold water to arrest any residual effects of heat exposure in order to gain accurate estimates of heating effects on microbial survival and death.…”
Section: Introductionmentioning
confidence: 99%